ESTIMASI BIOMASSA KARBON SERASAH DAN TANAHPADA BASAL AREA TEGAKAN MERANTI MERAH(Shorea macrophylla) DI AREAL ARBORETUMUNIVERSITAS TANJUNGPURA PONTIANAK - Budiman, M; Hardiansyah, Gusti; Darwati, Herlina (JURNAL HUTAN LESTARI, 2015)
Arboretum of Tanjungpura University rules as green buffer zone in the city to reduce the emision of Greenhouse Gases, especially carbon dioxide (CO2) and support processes such as producing life-supporting oxygen (O2) or lungs of the city. This research objective is to describe the diameter growth of Shorea macrophylla, measure carbon biomass potential litter and soil carbon in the basal area of stands of red meranti (Shorea macrophylla) in the Arboretum area Tanjungpura University Pontianak. This study uses a composite procedure in litter and soil sampling in the field to create a plot size of 0.5 x 0.5 meters as a plot of litter and soil in the basal area of ​​the stand Shorea macrophylla. The result of the growth of the average diameter increment per year on tree Shorea macrophylla ranging from 0.95 - 2.31 cm/year or had an average of 1.90 cm/year. The results of the carbon biomass of litter in the basal area of ​​the stand of red meranti (Shorea macrophylla) showed litter biomass ranged from 820.67 - 1630.44 g/m2 or have averaged 1159.89 g/m2. Meanwhile, the carbon stocks stored in the litter ranged from 415.99 - 804.94 g/m2with an average of 568 g/m2. Based on the results of research on the basal area of stands of red meranti (Shorea macrophylla) shows the percent soil organic carbon ranged from 4.60 - 5.63 %, or an average of 5.15 %. The results of the carbon stocks stored in the soil shows the variation ranged from 1.84 - 2.08 g/cm3, or by an average of 1.96 g/cm3. Keywords: Arboretum of Tanjungpura University, Shorea macrophylla, Carbon litter, soil carbon